FOOD SOVEREIGNTY: A NEW SOCIETAL PARADIGM FOR THE 21ST CENTURY? - M Rondhi; Nick Rose (UPT Penerbitan Universitas Jember, 2017)
“If we want to overturn the bleak situation of our current food system, we need to attack theroots of the problems. Injustice in land, water and seeds must be addressed. Stop land andwater grabbing and also patents of seeds. Genuine agrarian reform must be implemented. Weneed to focus to rural areas to address our hunger problem by restructuring our mode ofproduction to a more sustainable-agroecology farming. This is also to protect and restore ourMother Earth.”(Henry Saragih, former Global Coordinator of La Via Campesina, from his address delivered tothe 9th Asia-Europe People’s Forum held in October 2012). Our Time Has Come: Food Sovereignty Now!’, available at: http://viacampesina.org/en/index.php/main-issues- mainmenu-27/food-sovereignty-and-trade-mainmenu-38/1320-our-time-has-come-food-sovereigntynow